2014
DOI: 10.1002/14651858.cd002295.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Exercise interventions for smoking cessation

Abstract: Background Taking regular exercise may help people give up smoking by moderating nicotine withdrawal and cravings, and by helping to manage weight gain. Objectives To determine whether exercise-based interventions alone, or combined with a smoking cessation programme, are more effective than a smoking cessation intervention alone. Search methods We searched the Cochrane Tobacco Addiction Group Specialized Register in April 2014, and searched MEDLINE, EMBASE, PsycINFO, and CINAHL Plus in May 2014. Selection cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
84
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 210 publications
9
84
0
6
Order By: Relevance
“…Exercise can offer a useful treatment for smoking cessation (Ussher et al 2008), and a single session has consistently been shown to reduce cigarette cravings and withdrawal symptoms ). Even short moderate-intensity bouts have been shown to reduce cravings and cue reactivity and increase time to ad libitum smoking (Taylor and Katomeri 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise can offer a useful treatment for smoking cessation (Ussher et al 2008), and a single session has consistently been shown to reduce cigarette cravings and withdrawal symptoms ). Even short moderate-intensity bouts have been shown to reduce cravings and cue reactivity and increase time to ad libitum smoking (Taylor and Katomeri 2007).…”
Section: Introductionmentioning
confidence: 99%
“…La evidencia reporta que utilizar la AF como un elemento para dejar de fumar es débil, sin embargo, existe fuerte evidencia de que la AF reduce los síntomas de abstinencia, el deseo de fumar y el aumento de peso durante el abandono del tabaco. Por lo tanto, consejos para practicar AF deben ser incorporados en los programas para dejar de fumar 5,6,7 . Para un adulto sano, la oMS recomienda incrementar la AF tanto en el tiempo libre o de ocio, como en el trabajo y el traslado.…”
Section: En Chile Según La Encuesta Nacional De Salud 2009-10 El 88unclassified
“…Specifically, we sought to evaluate the extent to which specific types of PA, namely work-related and non-work-related PA, were associated with daily smoking intensity and urges. Given the increasing use of PA as an aid for smoking cessation among adults, 6,7 and more recently younger populations, 8,9 results of this study have direct implications for intervention.…”
mentioning
confidence: 91%